Tajikistan : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
This Country Financial Accountability Assessment (CFAA), the first for Tajikistan, is a key diagnostic study aimed at identifying the overall financial management risks. It's timing coincides with a meeting of the Tajik Consultative Group in April 2003, which pledged US$900 million of support over the next three years. Addressing the numerous, systemic financial management weaknesses in Tajikistan will have an important impact on the governance arrangements which, in turn, will affect donor disbursements against these commitments. In this respect, the CFAA also aims to provide a roadmap for future advice and technical assistance in public sector accountability. It assesses structural reforms in public sector budget management, accounting and financial reporting, the treasury system, internal controls and internal and external audits. I t also examines the mechanisms of public accountability at the sub-national and community levels.